Do Teaching Practices Impact Socio-emotional Skills? - Vaclav Korbel; Michal Paulus (Charles University in Prague, Institute of Economic Studies (IES), 2017)
Recent studies emphasize the importance of socio-emotional skills for the success in school as well as for later economic outcomes. However, little is known how practices used by teachers everyday in classrooms impact socio-emotional skills. We show that modern practices such as working in small groups improve them. Especially intrinsic motivation and self-confidence are positively affected. Moreover, modern practices have no adverse effects on test scores. Standard practices such as lecturing or memorizing have no impact on socio-emotional skills. Splitting the sample reveals detrimental effects of standard practices on socioemotional outcomes of boys and positive for high-achieving girls. On the contrary, both genders gain similarly from modern practices.
Keywords: I21; C23; 330; Teaching practices; socio-emotional skills; between-subject variation